Exploring the biotechnological applications of Spirulina maxima: a comprehensive review - J. C. Jacuinde-Ruíz; J. C. González-Hernández (Brazilian Journal of Biology)
Abstract The Spirulina maxima algae is a phototrophic, multicellular, filamentous cyanobacteria of greenish blue tones, without ramifications and is characterized mainly by its helical form, thickness of approximately 3 to 12 µm and length of 500 µm; its development depends on factors such as temperature, light intensity, pH, aeration speed, carbon dioxide concentration, carbon source, nitrogen source which determine its chemical composition, which is composed of proteins, carbohydrates, lipids, minerals, and vitamins; due to this, it is widely used in industries such as food, pharmaceutical, cosmetics, and energy to obtain different products of great value. This S. maxima review addresses morphological characteristics, growth factors, growth methods, and metabolites of biotechnological interest and biotechnological applications for the S. maxima microalgae. A brief review of the enzyme production capacity of S. maxima and other microalgae is also presented, in addition to mentioning some areas of opportunity to study these and the economic viability of implementing a biorefinery with an integrated approach for the production of biomass and metabolites of biotechnological relevance based on the control of growth variables and the productive and economic efficiency of the process is discussed.